2017
DOI: 10.1111/cbdd.13020
|View full text |Cite
|
Sign up to set email alerts
|

Quaternary ammonium salts substituted by 5‐phenyl‐1,3,4‐oxadiazole‐2‐thiol as novel antibacterial agents with low cytotoxicity

Abstract: Twenty-one novel 5-phenyl-1,3,4-oxadiazole-2-thiol (POT) substituted N-hydroxyethyl quaternary ammonium salts (6a-g, 7a-g, 8a-g) were prepared and characterized by FTIR, NMR, and elemental analysis. Compounds 6a, 6c, and 8a were confirmed by X-ray single-crystal diffraction. They display the unsurpassed antibacterial activity against Staphylococcus aureus, α-H-tococcus, Escherichia coli, P. aeruginosa, Proteus vulgaris, Canidia Albicans, especially 6g, 7g, 8g with dodecyl group. Compounds 8a-d with N,N-dihydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 36 publications
(40 reference statements)
0
12
0
Order By: Relevance
“…The antibacterial agent N -methyl-N-(5-phenyl-1,3,4-oxadiazole-2-thioethyl)- N , N -bis­(2-hydroxyethyl) quaternary ammonium salt was prepared according to our previous report. , The CS hydrogel (3 wt % in 1% acetic acid aqueous solution) was purchased from Shaanxi Renkang Pharmaceutical Co. Ltd. Fusidic acid cream (Aoluo) was purchased from Bright Future Pharmaceutical Factory (Hongkong, China). Balb/c mice (20 ± 2 g) or Sprague-Dawley (SD) rats (200 ± 20 g) were purchased from Beijing Vital River Laboratory Animal Technology Co., Ltd. (Beijing, China).…”
Section: Methodsmentioning
confidence: 99%
“…The antibacterial agent N -methyl-N-(5-phenyl-1,3,4-oxadiazole-2-thioethyl)- N , N -bis­(2-hydroxyethyl) quaternary ammonium salt was prepared according to our previous report. , The CS hydrogel (3 wt % in 1% acetic acid aqueous solution) was purchased from Shaanxi Renkang Pharmaceutical Co. Ltd. Fusidic acid cream (Aoluo) was purchased from Bright Future Pharmaceutical Factory (Hongkong, China). Balb/c mice (20 ± 2 g) or Sprague-Dawley (SD) rats (200 ± 20 g) were purchased from Beijing Vital River Laboratory Animal Technology Co., Ltd. (Beijing, China).…”
Section: Methodsmentioning
confidence: 99%
“…For example, the IC 50 values of 7a-d were orderly 44.26 ± 3.31 μg/mL, 16.78 ± 1.35 μg/mL, 12.90 ± 1.37 μg/mL, 5.08 ± 0.51 μg/mL for LO2 as well as 23.84 ± 2.13 μg/mL, 9.05 ± 0.92 μg/mL, 6.94 ± 0.53 μg/mL,4.16 ± 0.43 μg/mL for HaCat, respectively. These results indicated that their cytotoxicity and antimicrobial activities synchronously increased following the increased of chain length from hexyl group to dodecyl group 27 , and all of them exhibited weaker cytotoxicity compared with positive controls (BZK and CA). In addition, it should be pointed out that compounds 7d and POT-C12QAS ( 2 ) with POT and dodecyl group displayed weaker cytotoxicity than N -methyl- N -dodecyl- N,N -bis(2-hydroxyethyl) ammonium bromides (C12QAS), which IC 50 value was ca.…”
Section: Resultsmentioning
confidence: 81%
“…25 μg/mL against E. coli , Proteus vulgaris , P. aeruginosa , Table 1 ; MBC values were equal to corresponding MIC values, Table 2 ), other non-POT derivatives did not exhibit noticeable activities. Based on the above results, POT-QAS derivatives were partially superior to non-POT-QAS derivatives, and this might be because POT-QAS derivatives with flexible alkyl chain length and POT fragment could more easily pass through cell membrane into the cell to damage bacteria 20 , 27 , 30–32 .…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…The best derivative turned out to be tert-butyl, which showed moderate-to-good antibacterial and antifungal activity compared to benzalkonium chloride (BZK) and chlorhexidine acetate (CA) as positive controls. Researchers also tried to elucidate the possible mechanism of action, which could be puncturing the bacterial cell membrane and releasing the cytoplasm from the cell [73,74]. Among described derivatives some conclusions regarding the relationship structureactivity can be seen.…”
Section: Antibacterial Activity Of Amino Derivatives Of 134-oxadiazolementioning
confidence: 99%